Strawberry - Williams, Taniora (Te Kaharoa, 2019)
Peering out from behind the low clouds in the foggy night sky, the full moon’s light shone invitingly upon the back doorstep. As I sat under the silver tone of the moon, memories flooded my mind; the times when I was just a little girl eating strawberries that belonged to the crop next door. When no one was looking, I would go to the back of the yard where a tall wooden fence separated our house from the strawberry farm on the other side. If it wasn’t such a pretty fence, I would be annoyed with it. But I liked its colour, its smoothness, and its strength.